New Rural Access Index : Main Determinants and Correlation to Poverty - Iimi, Atsushi; Ahmed, Farhad; Anderson, Edward Charles; Diehl, Adam Stone; Maiyo, Laban; Peralta-Quiros, Tatiana; Rao, Kulwinder Singh (2016)
Transport connectivity is essential to sustain inclusive growth in developing countries, where many rural populations and businesses are still considered to be unconnected to the domestic, regional, or global market. The Rural Access Index is among the most important global indicators for measuring people’s transport accessibility in rural areas where the majority of the poor live. A new method to calculate the Rural Access Index was recently developed using spatial data and techniques. The characteristics of subnational Rural Access Index estimates were investigated in eight countries: Bangladesh, Ethiopia, Kenya, Mozambique, Nepal, Tanzania, Uganda, and Zambia. It was found that for the countries in Africa, road density and road condition are important determinants of the Rural Access Index. For the South Asian countries, improvement of road condition is particularly relevant. The evidence suggests that significant resources are likely to be required to achieve universal access through rehabilitating the existing road network and expanding the road network.